PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN PUZZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MATA PELAJARAN IPAS KELAS V DI SDN 2 GERIMAK INDAH - Mawaddah, Niswatun; Ramdhani Sucilestari; Hamzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low critical thinking skills of fifth grade students at SDN 2 Gerimak Indah. This was evident from the interview results, where students tended to provide very short answers to essay questions and were not yet able to explain their answers well. This condition was caused by the lack of innovation in the learning process carried out by teachers, resulting in students’ critical thinking skills not being developed optimally. To overcome this problem, the Problem Based Learning model assisted by puzzle media was applied in the IPAS subject. This study aimed to determine the effect of the Problem Based Learning model assisted by puzzles on students’ critical thinking skills in the fifth grade IPAS subject at SDN 2 Gerimak Indah. This study used a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The subjects of this study were students of class VA as the experimental class and class VB as the control class. The research data were collected through pretests and posttests using validated essay test instruments, and were supported by observation and documentation techniques. The data analysis techniques used included normality tests, homogeneity tests, and t-tests to test the research hypothesis. he results of the study showed that the Problem Based Learning model assisted by puzzles had a significant effect on students’ critical thinking skills. This was proven by the Mann–Whitney U test results (p = 0.007 and 0.008 < 0.05), indicating that was accepted, meaning that there was a difference between the experimental class and the control class. Therefore, the use of the Problem Based Learning model assisted by puzzles significantly affected students’ critical thinking skills in the fifth-grade IPAS subject at SDN 2 Gerimak Indah Keywords: Problem Based Learning and Critical Thinking Skills